2022
DOI: 10.53422/jdms.2022.91102
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Music Popularity Using Machine Learning Algorithm and Music Metrics Available in Spotify

Abstract: The exponential growth of online music streaming has given birth to many new platforms among which, the widely used platform is Spotify. The most popular music streaming app's data can be used to predict the capability of a song to be popular before its release with the help of attributes like loudness, energy, acousticness, etc. which is defined when the song is being made. This study helps to predict the popularity of the song using the song metrics available in Spotify by applying Random Forest classifier, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Which of these algorithms predicted popularity effectively was determined by looking at the accuracy, precision, recall, and F1-score metrics. When the results were examined, it was observed that the random forest algorithm gave the best result in estimating popularity [23].…”
Section: Literature Surveymentioning
confidence: 99%
“…Which of these algorithms predicted popularity effectively was determined by looking at the accuracy, precision, recall, and F1-score metrics. When the results were examined, it was observed that the random forest algorithm gave the best result in estimating popularity [23].…”
Section: Literature Surveymentioning
confidence: 99%
“…The musical representation used to define a hit song has different features. We noted works such as [Pareek et al 2022] that use previously processed high-level audio features, [Zangerle et al 2019] that utilized low-level audio features as a base to learn a deep representation, or some approaches that use pre-processing resources as Principal Component Analysis [Ge et al 2020] or autoencoders [Martín-Gutiérrez et al 2020]. The lyrics concentrate on important musical information and are also explored in [Singhi and Brown 2015;Martín-Gutiérrez et al 2020].…”
Section: Background and Related Workmentioning
confidence: 99%
“…OCL is relevant for the hit song prediction task because, considering the real music market scenario, we have few hit songs in relation to non-hit. This problem has been highlighted in MIR [Ge et al 2020;Martín-Gutiérrez et al 2020;Bertoni et al 2021;Pareek et al 2022] for hit-song prediction. However, it is explored as a problem with a dependency of non-hit songs.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation